Viral Vector Induction of CREB Expression in the Periaqueductal Gray Induces a Predator Stress-Like Pattern of Changes in pCREB Expression, Neuroplasticity, and Anxiety in Rodents - Robert Adamec; Olivier Berton; Waleed Abdul Razek (Neural Plasticity)
Predator stress is lastingly anxiogenic. Phosphorylation of CREB to pCREB (phosphorylated cyclic AMP response element binding protein) is increased after predator stress in fear circuitry, including in the right lateral column of the PAG (periaqueductal gray). Predator stress also potentiates right but not left CeA-PAG (central amygdala-PAG) transmission up to 12 days after stress. The present study explored the functional significance of pCREB changes by increasing CREB expression in non-predator stressed rats through viral vectoring, and assessing the behavioral, electrophysiological and pCREB expression changes in comparison with handled and predator stressed controls. Increasing CREB expression in right PAG was anxiogenic in the elevated plus maze, had no effect on risk assessment, and increased acoustic startle response while delaying startle habituation. Potentiation of the right but not left CeA-PAG pathway was also observed. pCREB expression was slightly elevated in the right lateral column of the PAG, while the dorsal and ventral columns were not affected. The findings of this study suggest that by increasing CREB and pCREB in the right lateral PAG, it is possible to produce rats that exhibit behavioral, brain, and molecular changes that closely resemble those seen in predator stressed rats.